An ensemble approach for portfolio selection in a multi-criteria decision making framework - Biswas, Sanjib; Bandyopadhyay, Gautam; Guha, Banhi; Bhattacharjee, Malay (Decision Making: Applications in Management and Engineering, 2019)
Investment in Mutual Funds (MF) has generated increasing interest among the investors over last few decades as it provides an opportunity for flexible and transparent choice of funds to diversify risk while having return potential. MF are essentially a portfolio wherein investors’ funds are invested in the securities traded in the capital market while sharing a common objective. However, selection and management of different asset classes pertaining to a particular MF are done by an active fund manager under regulatory supervision. Hence, for an individual investor, it is important to assess the performances of the MF before investment. Performances of MF depend on several criteria based on risk-return measures. Hence, selection of MF is subject to satisfying multiple criteria. In this paper, we have adopted an ensemble approach based on a two-stage framework. Our sample consists of the open ended equity large cap funds (direct plan) in India. In the first stage,the efficiencies of the funds are analyzed using DEA for primary selection of the funds. In order to rank the funds based on risk and return parameters for investment portfolio formulation, we have used MABAC approach in the second stage wherein criteria weights have been calculated using the Entropy method.